RECREATING THE GENRE PROPERTIES OF TEXTS IN TRANSLATION - Abdumajit Mamadaliev; Gulnoz Maksudova (Scholar Express Journal, 2023)
The article is devoted to recreating the genre properties of texts in translation, which is a vital task that requires careful consideration and skill. Genre properties encompass various elements, including style, tone, structure, narrative techniques, and thematic elements, which collectively contribute to the overall meaning and effect of a text. Preserving these genre properties in translation is essential to maintain the intended impact and engage the target audience effectively.
Keywords: genre properties; translation; challenges; complexities